Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00431-013-2128-y
|View full text |Cite
|
Sign up to set email alerts
|

Depression and adherence to treatment in diabetic children and adolescents: a systematic review and meta-analysis of observational studies

Abstract: This study showed moderate associations between depression and poor treatment adherence. Targeting behaviour and social environments, however, may ultimately provide more cost-effective health gains than targeting depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 53 publications
4
51
1
10
Order By: Relevance
“…In fact, depression is related to poor relationships and feelings of social isolation and to non-adherence to medical treatment across a range of chronic diseases, including hypertension [70][71][72][73][74]. Importantly, Krousel-Wood et al [44] found that at the univariate level both social support and depression were significantly related to adherence, whereas at the multivariate level (i.e., after controlling for their reciprocal effects) only depression remained a significant predictor of adherence.…”
Section: Limitations Of the Reviewed Literature And Suggestions For Fmentioning
confidence: 96%
“…In fact, depression is related to poor relationships and feelings of social isolation and to non-adherence to medical treatment across a range of chronic diseases, including hypertension [70][71][72][73][74]. Importantly, Krousel-Wood et al [44] found that at the univariate level both social support and depression were significantly related to adherence, whereas at the multivariate level (i.e., after controlling for their reciprocal effects) only depression remained a significant predictor of adherence.…”
Section: Limitations Of the Reviewed Literature And Suggestions For Fmentioning
confidence: 96%
“…Feelings of depression may be negatively related to adherence in children (Hood et al, 2006 ;Kongkaew, Jampachaisri, Chaturongkul, & Scholfi eld, 2014 ). Experiencing life stress and anxiety also can negatively impact adherence (Herzer & Hood, 2010 ).…”
Section: Disease Managementmentioning
confidence: 96%
“…The link between depression and DM can also have biological connections such as dyslipidaemia, which seems to be a biological correlate of depression and DM in adolescents 19 . There is preliminary evidence that higher levels of depression are associated with metabolic abnormalities and systemic inflammation 46 . T1D may contribute to emotional and biological disruptions, so that depression exacerbates dyslipidaemia 46 .…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…There is preliminary evidence that higher levels of depression are associated with metabolic abnormalities and systemic inflammation 46 . T1D may contribute to emotional and biological disruptions, so that depression exacerbates dyslipidaemia 46 . It is also assumed that depression itself is a moderate risk factor for developing DM in young adults, either directly or indirectly [47][48][49] .…”
Section: Biological Mechanismsmentioning
confidence: 99%